FINANCES OF ENTERPRISES - A. E. Nikiforov; V. M. Machulin; V. V. Titova (Литьë и металлургия)
Financial analysis of enterprise is given. Its task is to show how sources of financial assets of enterprise and areas of their using influence on chronic or periodically arising lack of cash assets